2014
DOI: 10.1051/0004-6361/201322889
|View full text |Cite
|
Sign up to set email alerts
|

Optical and near-IR observations of the faint and fast 2008ha-like supernova 2010ae

Abstract: A comprehensive set of optical and near-infrared (NIR) photometry and spectroscopy is presented for the faint and fast 2008ha-like supernova (SN) 2010ae. Contingent on the adopted value of host extinction, SN 2010ae reached a peak brightness of −13.8 > M V > −15.3 mag, while modeling of the UVOIR light curve suggests it produced 0.003-0.007 M of 56 Ni, ejected 0.30−0.60 M of material, and had an explosion energy of 0.04-0.30 × 10 51 erg. The values of these explosion parameters are similar to the peculiar SN 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
171
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(186 citation statements)
references
References 75 publications
14
171
1
Order By: Relevance
“…SN 2010ae was undetected up to five days before discovery . Using this limit, combined with data from Stritzinger et al (2014), we estimate a rise time to r-band maximum of 10 ± 2 d. Based on limited premaximum detections of SN 2007qd ), we estimate a rise time to r-band maximum of 11 ± 5 d. In addition to the above objects, we examined the unfiltered light curve of SN 2004cs presented by Foley et al (2013) and found a rise time of ∼9.0 ± 1.1 days. In order to estimate the rise time of SN 2008ha, Foley et al (2009) stretched the light curve of SN 2005hk, and found a rise time of ∼10 days to B-band maximum.…”
Section: Photometrymentioning
confidence: 90%
“…SN 2010ae was undetected up to five days before discovery . Using this limit, combined with data from Stritzinger et al (2014), we estimate a rise time to r-band maximum of 10 ± 2 d. Based on limited premaximum detections of SN 2007qd ), we estimate a rise time to r-band maximum of 11 ± 5 d. In addition to the above objects, we examined the unfiltered light curve of SN 2004cs presented by Foley et al (2013) and found a rise time of ∼9.0 ± 1.1 days. In order to estimate the rise time of SN 2008ha, Foley et al (2009) stretched the light curve of SN 2005hk, and found a rise time of ∼10 days to B-band maximum.…”
Section: Photometrymentioning
confidence: 90%
“…Their origin is still under discussion (e.g., Foley et al 2016). Although many of them have peak magnitudes brighter than −17 mag (see Foley et al 2016 for a summary) and are thus too bright to be ultra-stripped SNe, some of them do have fainter peak luminosity (e.g., Stritzinger et al 2014;McClelland et al 2010). We take one faint SN 2002cx-like SN, SN 2007qd (McClelland et al 2010, which is in the expected peak luminosity range for ultra-stripped SNe, and compare its spectrum at the peak luminosity with our synthetic spectra.…”
Section: Sn 2002cx-like (Type Iax) Snementioning
confidence: 99%
“…Using the empirical relation derived by Pettini & Pagel (2004) with the N2 index, we find a host metallicity of 12 + log(O/H) = 8. 2008ha, 2010ae, and 2012Z (Foley et al 2009Stritzinger et al 2014;Yamanaka et al 2015), respectively. SNe Iax therefore appear to show no preference for either sub-or super-solar 5 environments.…”
Section: Host Galaxy Metallicitymentioning
confidence: 99%
“…Most notably, SNe Iax can be fainter than normal SNe Ia (Li et al 2003) by up to five magnitudes (Valenti et al 2009;Foley et al 2009). They also display large variations in their light curve shapes, which show a broader range of decline rates 0.3 ∆m 15 (r) 1.1 (SN 2009ku, SN 2008ha, Narayan et al 2011Stritzinger et al 2014, respectively), and rise times, from ∼10 d (SN 2010ae, Stritzinger et al 2014;Magee et al 2016) to ∼22 d (SN 2005hk, Phillips et al 2007Magee et al 2016), when compared to normal SNe Ia. The fact that many SNe Iax have neither well-constrained peak magnitudes nor decline rates, and even fewer have secure rise time measurements, has further added to the difficulty in interpreting the observed behaviour of SNe Iax.…”
Section: Introductionmentioning
confidence: 99%